A experiência de professores(as) universitários(as) com ideações e/ou tentativas de pôr fim à vida. - Oliveira, Andréa Carla Ferreira de (2023)
Ending life, a theme full of prejudices and different motivations, has been a possibility of Dasein from the ancient to the contemporary world. Raised to the condition of public health problem, has affected the general population, among these, teachers, who have been suffering from significant changes in the work scenario in recent years, such as increased workload and precarious conditions. The starting point assumed in this work was to understand the experience of university professors with ideations and/or attempts to end existence in its singularity, removing any attempt to explain the phenomenon. The configuration of this study is of hermeneutic phenomenological research, inspired by the assumptions of the thought of Martin Heidegger and Hans-Georg Gadamer. Four professors from a federal public university were interviewed remotely due to the covid-19 pandemic and the restriction of face-to-face contact. The methodical path used the analysis of the narrative interviews of the participants and the researcher's affectations diary to understand the meaning of each one's experience. The professors signaled a collective tiredness, in which the ideation sums of ending existence may suggest a way to deal with suffering in the face of the sociopolitical dimension that guides the teaching projects of academic institutions. They narrated how they feel in the face of institutional impositions and precarious working conditions, which presented themselves as sources of illness and loss of meaning of the teaching project. In the folds of existence, ending of life presents itself as a possibility for teachers, when they cannot control adverse situations, such as a restlessness of the Dasein that lies in the "between" of the mystery life and death, leading them to decide at all times how to exist in the face of what happens in the various dimensions of life.